Exploring the Impact of Computer-Based Hybrid Dynamic Assessment on EFL Students’ Academic Writing Development - Dayat, Dayat; Mustiah, Mustiah; Meliasari, Rahayu (Journal of Languages and Language Teaching, 2025)
Little attention has been paid to the computer-based hybrid dynamic assessment (C-HDA) in the context of English as a foreign language (EFL) academic writing. However, This study aimed to examine the impact of C-HDA in improving the writing skills of Indonesian higher education students. A sequential explanatory mixed-methods design was employed. To gather quantitative data, one-group pretest-posttest research design was employed. Qualitatively, semi-structured interviews with the experimental group were also conducted to investigate the extent to of mediation benefited the participants during the teaching session. The interview was conducted after the post-test was completed accordingly. Eleven of twenty-two aged 19-20 years old enrolled in the Writing for Academic Purposes course and participated in this research project. The participants were required to write an argumentative essay of 150-300 words consisting of three paragraphs (introduction, body, and conclusion) and their essays were then assessed by using the recent C-HDA. All essays were, then, scored (by three raters) based on five criteria of academic writing, content, organization, language use, mechanics, and style. T-test and the thematic analysis were used to analyze the quantitative and qualitative data, respectively. The results showed that the the current C-HDA improved the participantsâ€™ academic writing although no maximal score was achieved. In addition, the qualitative data found three themes, positive and negative perspectives, and suggestions that addressed the participantsâ€™ perceptions toward the C-HDA. This study yields implications for academic writing teachers about the implementation of C-HDA in developing academic writing for low-competent students.Â